Peran Humas Pencak Silat Nahdlatul Ulama Pagar Nusa dalam Membangun Hubungan dengan Warga - Haq, Fitri Rahmatulloh Nur; Moch. Arkansyah (DIGICOM : Jurnal Komunikasi dan Media, 2024)
The Pencak Silat Nahdlatul Ulama Pagar Nusa's Role of Public Relations in Fostering connections with Gebang Putih Subdistrict, Surabaya City, essentially has a role and a plan of its own in fostering connections with the people living in Gebang Putih Subdistrict, Surabaya City. At PSNU Pagar Nusa Gebang Putih, public relations initiatives are typically coordinated within the organization as a whole, making use of available resources to accomplish certain objectives. According to the findings of the Excellence theory analysis, public relations is seen as a profession that plays the role of a manager who employs dialogue and research to build positive relationships with the public in addition to acting as a communicator and persuasive tool to spread information.